STATEMENT OF THE CMI THEOLOGICAL FORUM Indian Ecclesia: An Inter-religious Community - Kalliath, Antony (Journal of Dharma, 1999)
We, thirty three members of the Carmelites of Mary Immaculate (CMI) held a colloquium from Feb. 4 to 7, 1999, at Dharmaram Vidya Kshetram, Bangalore which was the first meeting of the CMI Theological Forum on the theme: Indian Ecclesia: An Interreligious Community.